German soldiers and the occupation of France, 1940-1944 - Torrie, Julia S. 1973- (Studies in the social and cultural history of modern warfare, 2018)
Occupations past and present -- Consuming the tastes and pleasures of France -- Touring and writing about occupied land -- Capturing experiences: and photo books -- Rising tensions -- Westweich perceptions of "softness"; among soldiers in France -- Twilight of the gods